2016
DOI: 10.5194/soil-2-83-2016
|View full text |Cite
|
Sign up to set email alerts
|

Soil properties and not inputs control carbon : nitrogen : phosphorus ratios in cropped soils in the long term

Abstract: Abstract. Stoichiometric approaches have been applied to understand the relationship between soil organic matter dynamics and biological nutrient transformations. However, very few studies have explicitly considered the effects of agricultural management practices on the soil C : N : P ratio. The aim of this study was to assess how different input types and rates would affect the C : N : P molar ratios of bulk soil, organic matter and microbial biomass in cropped soils in the long term. Thus, we analysed the C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 85 publications
2
26
0
Order By: Relevance
“…Other studies have observed that adding additional phosphorus and sulfur at the time of residue C incorporation increased SOC throughout a 1.6 m soil profile (Frossard et al, ; Kirkby, Richardson, Wade, Conyers, & Kirkegaard, ). The SOC increases we observed throughout the 2 m profile may have been similarly facilitated by the relatively large amounts of P, S (>25 kg/t) and other nutrients applied in the poultry manure compost alongside compost‐C inputs.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Other studies have observed that adding additional phosphorus and sulfur at the time of residue C incorporation increased SOC throughout a 1.6 m soil profile (Frossard et al, ; Kirkby, Richardson, Wade, Conyers, & Kirkegaard, ). The SOC increases we observed throughout the 2 m profile may have been similarly facilitated by the relatively large amounts of P, S (>25 kg/t) and other nutrients applied in the poultry manure compost alongside compost‐C inputs.…”
Section: Discussionmentioning
confidence: 90%
“…Increased soil available N provided by the leguminous WCC may have increased the microbial use efficiency of WCC-C inputs, leading to greater incorporation of WCC-C into microbial bodies and ultimately greater soil organic C pools (Lange et al, 2015). Other studies have observed that adding additional phosphorus and sulfur at the time of residue C incorporation increased SOC throughout a 1.6 m soil profile (Frossard et al, 2016;Kirkby, Richardson, Wade, Conyers, & Kirkegaard, 2016). The SOC increases we observed throughout the 2 m profile may have been similarly facilitated by the relatively large amounts of P, S (>25 kg/t) and other nutrients applied in the poultry manure compost alongside compost-C inputs.…”
Section: Discussionmentioning
confidence: 99%
“…The breakup of aggregates made the soils finer (Costa et al ., ; Tebebu et al ., ). This then resulted in both more leaching of nutrients (Frossard et al ., ) and greater sediment concentrations in surface runoff (Fernández‐Sanjurjo, ; Tebebu et al ., ; Zhang et al ., ). To maintain crop yield, fertilizer and pesticide use increased, leading to even greater nutrient losses (Tilman et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, nutrient depletion, land degradation, and water quality under continuous cultivation after deforestation are strongly related. While the effect of nutrient depletion on land degradation has been well researched (Drechsel et al ., ; Oenema et al ., ; Frossard et al ., ), less is known with respect to water quality and eutrophication.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural soils are a source of CO 2 emission around the world, and this is accompanied by mismanagement that results in high erosion rates, soil aggregate loss, low infiltration rates, and changes in the soil biota (Bruun et al, 2015;Choudhury et al, 2016;de Moraes Sá et al, 2015;de Oliveira et al, 2015;Frossard et al, 2016;Gelaw et al, 2015;Leifeld and Mayer, 2015). The impact of CO 2 on global warming has resulted in a growing interest in reducing emissions and increasing sequestration, and soil can be a good sequestration option under appropriate management (Carr et al, 2015;Ferreira et al, 2016;Hu et al, 2015;Hombegowda et al, 2016;Poeplau et al, 2016).…”
Section: Introductionmentioning
confidence: 99%